The Influence of Macroeconomic Indicators on Economic Growth in Malaysia - Nur Hazirah, Md Ludin (2011)
One aim in macroeconomic policy is to achieve higher economic growth. The objective of this study is to examine the influence of macroeconomic variables in determining economic growth. In this study, technique Dickey–Fuller, cointegration, Granger test and Vector Error Correction Model (VECM) will be use. The function of co integration test is to test the existence long-term relationship between the variable in the model. The period of time series data are from 1976 to 2008. Four macroeconomic variables will be using which are consumer price index, foreign direct investment (FDI), total government expenditure, and total export in Malaysia. Last result shows that exist 2 cointegrating equations at 5% level in Johansen cointegration test. Only FDI, CPI and government expenditure have one way causality with GDP. While export and GDP does not Granger cause each other. In VECM test, the value of the coefficient in this error correction term is exceed than 1, it shows that the short-run deviation goes rapid paths to the equilibrium in the long-run. It is important for government to take care the significant macroeconomic factors in this analysis in order to achieve a higher growth rate in future. Export diversification is the key in increasing the total of export. It will various the Malaysia product and help to expand Malaysia’s export earnings.